Polynitroxylated PEGylated hemoglobin protects pig brain neocortical gray and white matter after traumatic brain injury and hemorrhagic shock - Wang, Jun; Shi, Yanrong; Cao, Suyi; Liu, Xiuyun; Martin, Lee J.; Simoni, Jan; Soltys, Bohdan J.; Hsia, Carleton J. C.; Koehler, Raymond C. (Frontiers in Medical Technology, 2023)
Polynitroxylated PEGylated hemoglobin (PNPH, aka SanFlow) possesses superoxide dismutase/catalase mimetic activities that may directly protect the brain from oxidative stress. Stabilization of PNPH with bound carbon monoxide prevents methemoglobin formation during storage and permits it to serve as an anti-inflammatory carbon monoxide donor. We determined whether small volume transfusion of hyperoncotic PNPH is neuroprotective in a porcine model of traumatic brain injury (TBI) with and without accompanying hemorrhagic shock (HS). TBI was produced by controlled cortical impact over the frontal lobe of anesthetized juvenile pigs. Hemorrhagic shock was induced starting 5 min after TBI by 30 ml/kg blood withdrawal. At 120 min after TBI, pigs were resuscitated with 60 ml/kg lactated Ringer's (LR) or 10 or 20 ml/kg PNPH. Mean arterial pressure recovered to approximately 100 mmHg in all groups. A significant amount of PNPH was retained in the plasma over the first day of recovery. At 4 days of recovery in the LR-resuscitated group, the volume of frontal lobe subcortical white matter ipsilateral to the injury was 26.2 ± 7.6% smaller than homotypic contralateral volume, whereas this white matter loss was only 8.6 ± 12.0% with 20-ml/kg PNPH resuscitation. Amyloid precursor protein punctate accumulation, a marker of axonopathy, increased in ipsilateral subcortical white matter by 132 ± 71% after LR resuscitation, whereas the changes after 10 ml/kg (36 ± 41%) and 20 ml/kg (26 ± 15%) PNPH resuscitation were not significantly different from controls. The number of cortical neuron long dendrites enriched in microtubules (length >50 microns) decreased in neocortex by 41 ± 24% after LR resuscitation but was not significantly changed after PNPH resuscitation. The perilesion microglia density increased by 45 ± 24% after LR resuscitation but was unchanged after 20 ml/kg PNPH resuscitation (4 ± 18%). Furthermore, the number with an activated morphology was attenuated by 30 ± 10%. In TBI pigs without HS followed 2 h later by infusion of 10 ml/kg LR or PNPH, PNPH remained neuroprotective. These results in a gyrencephalic brain show that resuscitation from TBI + HS with PNPH protects neocortical gray matter, including dendritic microstructure, and white matter axons and myelin. This neuroprotective effect persists with TBI alone, indicating brain-targeting benefits independent of blood pressure restoration.